2000
DOI: 10.1109/50.827518
|View full text |Cite
|
Sign up to set email alerts
|

Efficient time-domain finite-difference beam propagation methods for the analysis of slab and circularly symmetric waveguides

Abstract: Abstract-The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 14 publications
1
13
0
2
Order By: Relevance
“…This fact becomes more significant for a higher dimensional problem. Therefore, consideration is next given to the applications of the HABC and C-COM to the 2-D TD-BPM based on the alternating-direction implicit method (ADIM) [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This fact becomes more significant for a higher dimensional problem. Therefore, consideration is next given to the applications of the HABC and C-COM to the 2-D TD-BPM based on the alternating-direction implicit method (ADIM) [15].…”
Section: Discussionmentioning
confidence: 99%
“…It is found that the C-COMs with three and four boundary cells are comparable to the PMLs with eight and 16 cells, respectively. The effectiveness of the C-COM is also demonstrated for the two-dimensional (2-D) TD-BPM [15].…”
Section: Introductionmentioning
confidence: 99%
“…Many analyses of such waveguides combine the BPM method with other algorithms to take account of the reflected waves. For instance, FDTD-BPM [1,2], combining the BPM with FDTD method, the bidirectional eigenmode propagation method using the finite element method [3] for a fiber grating, and the time domain BPM method [4] based on the finite element method for a periodic optical waveguide with rectangular cross section, have been applied to cases in which the number of grating periods is comparatively small.…”
Section: Introductionmentioning
confidence: 99%
“…Many analyses of such waveguides combine the BPM method with another algorithm to take account of the reflected waves. For instance, FDTD-BPM [1,2], combining the BPM with the FDTD method, the bidirectional eigenmode propagation method using the finite element algorithm [3] for a fiber grating, and the time domain BPM method [4] based on the finite element method for a periodic optical waveguide with a rectangular cross section, have been applied to cases in which the number of grating periods is small. In the case of large periods, Floquet's theorem has been introduced into the BPM method based on MOL in order to analyze twodimensional periodic optical waveguides [5].…”
Section: Introductionmentioning
confidence: 99%